Epidemiology of chronic thromboembolic pulmonary hypertension (CTEPH) in the Czech Republic. (28th March 2022) - Jansa, Pavel; Ambrož, David; Kuhn, Matyáš; Dytrych, Vladimír; Aschermann, Michael; Černý, Vladimír; Gressin, Virginie; Heller, Samuel; Kunstýř, Jan; Širanec, Michal; Song, Ci; Linhart, Aleš; et al.
Abstract: This study investigated the epidemiology and survival outcomes of chronic thromboembolic pulmonary hypertension (CTEPH) in the Czech Republic, wherein pulmonary endarterectomy (PEA) surgery was the only targeted treatment option until 2015. This study included all consecutive adults newly diagnosed with CTEPH in the Czech Republic between 2003 and 2016. Incidence/prevalence rates were calculated using general population data extracted from the Institute of Health Information and Statistics of the Czech Republic. Kaplan–Meier estimates of survival from diagnosis until 2018 were calculated. Of a total of 453 patients observed, 236 (52.1%) underwent PEA (median time from diagnosis to PEA: 2.9 months) and 71 (34.1%) had residual pulmonary hypertension (PH) post‐PEA. CTEPH incidence rate (95% confidence interval [CI]) between 2006 and 2016 was 4.47 (4.05; 4.91) patients per million (ppm) per year, and the prevalence (95% CI) was 37.43 (33.46; 41.73) ppm in 2016. The rate of CTEPH‐related hospitalizations (95% CI) per 100 person‐years was 24.4 (22.1; 26.9) for operated patients and 34.2 (30.9; 37.7) for not‐operated patients. Median overall survival (95% CI) for all patients from CTEPH diagnosis was 11.2 (9.4; not reached) years. Five‐year survival probability (95% CI) was 95.3% (89.9; 97.9) for operated patients without residual PH, 86.3% (75.3; 92.7) for operated patients with residual PH and 61.2% (54.0; 67.6) for not‐operated patients. This study reported epidemiological estimates of CTEPH in the Czech Republic consistent with estimates from other national systematic registries; and indicates an unmet medical need in not‐operated patients and operated patients with residual PH.